Facing up the primary emotions in Mobile Software Ecosystems from Developer Experience - Fontão, Awdren; Ekwoge, Oswald M.; Santos, Rodrigo; Dias-Neto, Arilo Claudio (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2017)
Mobile application 1developers use Questions and Answers (Q&A) repositories, such as Stack Overflow, to solve technical issues when developing their mobile applications. In this formed ecosystem, Q&A repositories can serve as a mechanism to analyze the experiences during mobile application development. Regarding developers' feelings about work, we can analyze the emotions involved in developer experience by mining developers' questions. We used 1,568,377 body of posts from Stack Overflow related to Android, iOS and Windows to perform comparisons among the three ecosystems regarding the emotions: Joy, Fear, Sadness, Anger, and Disgust. Our results indicate that Sadness, Anger and Joy are the most common emotions. We also identified which technical elements are involved in these emotions.